2015
DOI: 10.1177/1066896915600518
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular and Vascular Hamartoma of the Small Intestine

Abstract: The term Neuromuscular and Vascular Hamartoma (NMVH) was initially coined by Fernando and McGovern in 1982 in their report of 2 cases. Whether this lesion is truly hamartomatous or represents a "burnt-out" phase of varying chronic pathologies has been debated since that time. Examples of NMVH-like proliferations have been reported in the setting of diaphragm disease, Crohn's disease, radiation, and ischemia. Herein we present the case of a 73-year-old female with partial small bowel obstruction and a past surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…Similar histological features have been seen in association with a range of chronic reactive conditions, and it has been suggested that the NMVH is not a distinct entity, but is in fact a ‘burnt out’ form of Crohn’s disease or another chronic inflammatory process [2] , [3] , [6] . NMVH-like proliferations have been described in relation to diaphragm disease, radiation enteritis, ischaemic enteritis, and Crohn’s disease.…”
Section: Introductionmentioning
confidence: 73%
See 4 more Smart Citations
“…Similar histological features have been seen in association with a range of chronic reactive conditions, and it has been suggested that the NMVH is not a distinct entity, but is in fact a ‘burnt out’ form of Crohn’s disease or another chronic inflammatory process [2] , [3] , [6] . NMVH-like proliferations have been described in relation to diaphragm disease, radiation enteritis, ischaemic enteritis, and Crohn’s disease.…”
Section: Introductionmentioning
confidence: 73%
“…However, their cases showed an absence of fissuring ulceration and transmural inflammation, both of which are typical hallmarks of active Crohn’s disease. They suggested that the particular pathological features seen in their four cases may be those of a chronic, ‘burnt out’ form of Crohn’s disease [3] , [6] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations